Evolving healthcare; nurses' attitudes towards complementary therapies. (30th September 2020) - Hall, H; Leach, M; Brosnan, C; Collins, M
Abstract: Background: Integration of complementary therapies alongside conventional medical treatment is common and affects health behaviour and outcomes. Nurses frequently interact with patients and their attitudes to these therapies may play a significant role in decision-making. This mixed-method study investigated nurses' attitudes and behaviour towards complementary therapies. Methods: A sequential exploratory design was utilised. Qualitative data were collected via interviews with nurses working in primary and tertiary settings, in all states of Australia. Interview data underwent thematic analysis. Findings from the interviews informed the development of a questionnaire, which was used to conduct a national online survey. Survey data were descriptively analysed using frequency distributions and percentages. Results: Nineteen nurses were interviewed and 614 responded to the survey. Themes that emerged from the qualitative data were; Promoting safe care, Seeking complementary therapies knowledge; Supporting holistic health care and Integrating complementary therapies in practice. Survey responses revealed most nurses (77.5%) discussed complementary therapies with patients. More than one half (55.5%) would 'sometimes' recommend complementary therapies and 12.0% would 'almost always/always' do so. The majority (91.8%) believed nurses should have some understanding of complementary therapies. There was a lack of agreement regarding integration of these therapies into nursing practice. Conclusions: Nurses were generally supportive of patients' interest in complementary therapies and want basic education about these therapies. Key messages: Nurses working in Australia often engage with patients about complementary therapies. Increasing nurses' complementary therapy knowledge is likely to promote informed decision-making and improve patient safety.